Simultaneous determination of Diazinon, Malathion and Quinalphos pesticide formulations by gas chromatography with an electron capture detector - Asha K.L.; Tan G.H.; Chai M.K. (2023)
A gas chromatography (GC) method has been developed to analyze simultaneously separate formulations of Diazinon, Malathion and Quinalphos with the internal standard method. A mixture of pure standard solution spiked with Chlorpyrifos as the internal standard and diluted with methanol was sonicated to homogenize the solutions. A 2?L volume of the mixture standard solution was injected into the GC-ECD and a six point calibration curve that demonstrated a linear range was established for each target compound. Samples of each formulation, mixed with the internal standard and diluted with methanol were injected into the GC-ECD. Combinations of three different concentrations of each formulated pesticide were analyzed six times to obtain coefficients of variation which are less than 1%. The total analysis time for each run was 15 minutes. The concentration of active ingredients in the pesticide formulations were calculated from the peak area values at a retention time interpolated from the calibration graphs. The analytical results which show 55.41 0.82% for Diazinon, 83.97 0.36% for Malathion and 10.89 0.89 % for Quinalphos were within the specifications for these commercial pesticide formulations.